Persepsi Siswa Vokasi terhadap Sarana dan Prasarana Bengkel Instalasi Motor Listrik di Sekolah - Salsa Mei Indah Gayatri; Hambali Hambali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
Facilities and infrastructure in practical activities become one of the factors in the learning process in order to achieve learning goals in schools. The purpose of this study was to determine students' perceptions of the facilities and infrastructure of the Electric Motor Power Installation Workshop. This study used population and sample, the population in this study were students of class XII TITL SMK Negeri 5 Padang while the sample used Nonprobability sampling with a total of 88 students. The results of the study used the overall percentage value regarding students' perceptions of the facilities and infrastructure of the electric motor installation workshop in SMK Negeri 5 Padang is included in the good category. The percentage is obtained from the calculation results of the three existing indicators. Indicators of students' knowledge of electrical installation workshop facilities and infrastructure are in the good category, indicators of student experience in carrying out electrical installation practices are in the good category, and indicators of electrical workshop facilities and infrastructure are also in the good category.